ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI TERJADINYA FINANCIAL DISTRESS PADA PEMERINTAH DAERAH - Nurjannah, Nurjannah; Ningsih, Endang Surasetyo (Universitas Sang Bumi Ruwa Jurai, 2025)
The purpose of this study was to determine the effect of financial ratios (Solvency Ratio, Degree of Fiscal Decentralization, and Financial Independence Ratio) on financial distress in local governments. The type of research used is quantitative research. The population in this study is 23 districts/cities in Aceh Province. The data used in this study is secondary data in the form of Regional Government Financial Reports for 2017, 2018, and 2019 obtained from the Indonesian Financial Audit Agency (BPK-RI) representative of the Aceh Province. The analysis technique used is multiple linear regression analysis. The results showed that the solvency ratio, the degree of fiscal decentralization and the ratio of financial independence simultaneously had an effect on financial distress. Partially, the solvency ratio and the degree of fiscal decentralization have no effect on financial distress. while the ratio of financial independence has a negative effect on financial distress.